Creativity, Sociability, Solidarity: New-Wave Carnival Krewes’ Responses to COVID-19 in New Orleans - Radice, Martha (Anthropologica, 2021)
New Orleans was one of the first cities in the USA to be severely affected by the COVID‑19 pandemic. This article draws on long-term ethnography and recent remote fieldwork to explore how new-wave carnival krewes in New Orleans responded to the pandemic. New-wave krewes are one of the kinds of social clubs that produce carnival each year. During the first four months of the pandemic, some of them undertook various kinds of projects within their membership and in the broader community. I propose that these projects have three overlapping dimensions: creativity, sociability, and solidarity. My argument is that because they are so enmeshed in the social fabric of New Orleans, new-wave carnival krewes provided a solid foundation for social initiatives that sought to alleviate the existential and material insecurity of the pandemic. I further argue that carnival has emerged as an important way for New Orleanians to make the imaginative connection between the personal and the social that is necessary for grasping the scope of COVID‑19. More broadly, I contribute to what Joel Robbins has called an “anthropology of the good” in social relations.